Herpes simplex virus type 2 infection in pregnancy: asymptomatic viral excretion at delivery and seroepidemiologic survey of two socioeconomically distinct populations in São Paulo, Brazil - Weinberg, Adriana; Canto, Cynthia L.M.; Pannuti, Claudio S.; Kwang, Wu N.; Garcia, Sidney A.L.; Zugaib, Marcelo (Revista do Instituto de Medicina Tropical de São Paulo, 1993)
The objective of the present study was to estimate the prevalence of herpes simplex virus type 2 (HSV 2) antibodies in child bearing women of 2 Brazilian populations with different socioeconomic status and to determine the risk of neonatal HSV exposure by means of maternal cultures at the onset of labor. The study was conducted at 2 hospitals: A, serving very low income patients and B, serving middle socioeconomic class. 173 participants from group A and 127 from B answered a questionnaire which showed that the patients had similar ages (27.7 and 26.8 years, respectively) but differed with regard to socioeconomic status, age at first intercourse (18.6 vs 20.6 years), number of sex partners (1.5 vs 1.2) and previous sexually transmitted diseases (15% vs. 1.5%). History of genital herpes was given by 11% of group A participants and by a similar number, 7%, of patients from group B. In addition, 200 serum samples from population A and 455 from B were tested by ELISA for and HSV antibodies and 92% and 86%, respectively, were found to be positive. Sixty seropositive samples from group A and 90 from B were further analyzed by Western blot, which showed the presence of type 2 specific antibodies in 46% and 36%, respectively, suggesting an overall HSV 2 prevalence of 42% in group A and 31% in B. Cervical specimens were obtained for culture from 299 asymptomatic patients of population A and 313 of B. HSV was isolated from one specimen in each group, indicating a 0.3% incidence of asymptomatic viral excretion in both populations. In conclusion, the prevalence of type 2 antibodies in childbearing women was very high, but it did not differ with the socioeconomic status. The risk of HSV perinatal transmission was also similar in the 2 study populations and it was comparable with the data from developed countries. Our findings do not indicate the need of special screening programs for asymptomatic HSV excretion in Brazilian pregnant women.